Mahmudhoja Behbudi and his work Qasdi safar - Dilafruz Rakhmatova; Saodat Sattarova (Research Parks Publishing LLC, 2021)
The social, political, economic, cultural and educational changes that took place in Turkestan in the late 19th and early 20th centuries were one of the first steps towards independence. Our Jadids, especially Mahmudkhoja Behbudi, have shown great interest in studying his life and work. Mahmudhoja Behbudi was both a publisher, a journalist, and the founder of Uzbek drama, not only a geographer, but also a skilled politician. In particular, in more than 300 articles he speaks about language issues, social problems, our traditions, school life, which he did not overlook during his travels to the Middle East, and the travels of Turkestan pilgrims.’’ Qasdi Safar’’ is a unique travelogue that has a place among created the memoirs in the East.